Delinking land rights from land use: Certification and migration in Mexico. - De Janvry, Alain.; Emerick, Kyle.; Gonzalez-Navarro, Marco, 1979-; Sadoulet, Elisabeth, 1945- (Tufts University. Tisch Library., 2018)
In many developing countries property rights over rural land are maintained through continuous personal use instead of by land titles. We show that removing the link between land use and land rights through the issuance of ownership certificates can result in large-scale adjustments to labor and land allocations. Using the rollout of the Mexican land certification program from 1993 to 2006, we find that households obtaining certificates were subsequently 28 percent more likely to have a migrant member. We also show that even though land certification induced migration, it had little effect on cultivated area due to consolidation of farm units.